2018
DOI: 10.1002/zoo.21401
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of wounding in hamadryas baboons (Papio hamadryas) in North American zoos

Abstract: In North American zoos, hamadryas baboons (Papio hamadryas) have traditionally been housed as single one-male units (single male groups). In recent years, efforts have been made to house hamadryas in groups composed of multiple one-male units (multi-male groups) to more closely mirror their natural social structure, in addition to all-male or bachelor groups to manage surplus males. Given that the majority of social conflict in hamadryas occurs between males during the acquisition and defense of females, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Despite the agonistic tendencies reported for Japanese macaques, the wounding rate reported here (4.6 wounds annually per individual, on average) is similar to the rate reported recently in a multi‐zoo study of gorilla wounding (4.8 wounds per year; Leeds et al, 2015), and less than half the rate reported in an earlier study of chimpanzee wounding (9.48 wounds per year; Ross et al, 2009). Japanese macaques did receive more wounds than hamadryas baboons; however (3.36 wounds per year; Wiley et al, 2018). Japanese macaques are typically characterized as very low tolerance with high rates of aggressive interactions, unlike gorillas and chimpanzees; therefore, these comparative patterns highlight the potential for a dissociation between aggressive behavior and wounding.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite the agonistic tendencies reported for Japanese macaques, the wounding rate reported here (4.6 wounds annually per individual, on average) is similar to the rate reported recently in a multi‐zoo study of gorilla wounding (4.8 wounds per year; Leeds et al, 2015), and less than half the rate reported in an earlier study of chimpanzee wounding (9.48 wounds per year; Ross et al, 2009). Japanese macaques did receive more wounds than hamadryas baboons; however (3.36 wounds per year; Wiley et al, 2018). Japanese macaques are typically characterized as very low tolerance with high rates of aggressive interactions, unlike gorillas and chimpanzees; therefore, these comparative patterns highlight the potential for a dissociation between aggressive behavior and wounding.…”
Section: Discussionmentioning
confidence: 97%
“…The methods of this study were modeled after previous studies investigating the factors associated with wounding in zoo‐housed primates (Leeds et al, 2015; Ross et al, 2009; Wiley et al, 2018). Each participating institution received a detailed set of instructions in June 2016 and care staff at the institution were advised to record all incidences of wounding observed ad libitum beginning as soon as their institutional practices allowed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, captive protocols require zoo staff to step in if aggression becomes so extreme in frequency or severity that it affects the welfare of the animals (AZA, 2020, p. 13; Minier, personal communication, 2/20/2020). In addition, wounding rates in hamadryas baboons are low in captivity (Wiley et al, 2017). Our results show that aggression between the two subadult males and the alpha male did occur over the 6 months, but did not increase during the project timeline, even after Kusa formed his OMU with Kodee.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while there is no competition between neighboring bands in captivity, there is still the potential for competition between sexually maturing males within one clan if multiple OMUs are housed together in an exhibit. Despite the potential for increased aggression, in recent years, the hamadryas Species Survival Plan (SSP®) has encouraged the formation of several OMUs in one larger social group in captivity, as this will more closely resemble the wild social environment (Wiley et al, 2017). Therefore, finding appropriate ways to manage and understand key life‐history moments and species‐specific behaviors of these monkeys is a necessity for captive populations.…”
Section: Introductionmentioning
confidence: 99%